Temperature distribution measurement inside an Er:Yb:Lu2Si2O7 crystal under 1.55 μm laser operation. (November 2022) - Chen, Qijun; Huang, Jianhua; Huang, Yidong; Lin, Fulin; Lin, Yanfu; Gong, Xinghong; Luo, Zundu; Chen, Yujin
Highlights: Temperature measurement inside the laser crystal was performed based on the fluorescence intensity ratio technique. Polarized up-conversion fluorescence spectra in 500–580 nm of an Er:Yb:Lu2 Si2 O7 crystal were measured at 300–680 K. Temperature distribution inside an Er:Yb:Lu2 Si2 O7 crystal was measured in real time when a 1.55 μm laser was operating. The experimental result was compared with the theoretical temperature distribution inside the crystal. Abstract: Based on the fluorescence intensity ratio technique, the temperature distribution inside an Er:Yb:Lu2 Si2 O7 crystal was measured in real time when a 1.55 μm laser was operating. The polarized green up-conversion fluorescence in 500–580 nm of the crystal generated simultaneously under laser operation was used as the temperature probe. At a pump beam waist diameter of 400 μm, the highest temperature inside the crystal reached 507 K when the incident pump power and output mirror transmission were 11.13 W and 1.3%, respectively. The experimental result was compared with the theoretical temperature distribution inside the crystal simulated by the finite element analysis method, and the difference between them was analyzed.